PROSPECTS OF SIMULATION TRAINING IN HIGHER MEDICAL EDUCATION - Rakhimov Abduraim Fazilovich (Scholar Express Journals, 2023)
The article deals with the importance of using phantoms, and mannequins (simulators) within the framework of the 4-step method in training cadets and trainees at a military higher medical educational institution. The purpose of the research is to compare the traditional (theoretical and practical) method of conducting practical training with the 4-step method of simulation training using phantoms, and mannequins (simulators) that are close to reality, and to evaluate their effectiveness. 54 cadets and listeners participated in this process, who were divided into 2 groups. The results confirmed that the effectiveness of simulation training within the framework of the 4-step method is much higher than traditional training.
Keywords: phantom; mannequin; robot-simulators; 4-step method